2000
DOI: 10.2307/2653611
|View full text |Cite
|
Sign up to set email alerts
|

Iceberg Epistemology

Abstract: Accounts of what it is for an agent to be justified in holding a belief commonly carry commitments concerning what cognitive processes can and should be like. A concern for the plausibility of such commitments leads to a multi-faceted epistemology in which elements of traditionally conflicting epistemologies are vindicated within a single epistemological account. The accessible and articulable states that have been the exclusive focus of much epistemology must constitute only a proper subset of epistemological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
(16 reference statements)
0
27
0
Order By: Relevance
“…Such automatically accommodated implicit information is called morphological content (Horgan and Tienson 1996, Potrč 1999, 2000, Henderson and Horgan 2000. Transglobal evidentialism-reliabilism gives pride of place to the notion of strong evidential support, as explicated non-reliabilistically in terms of truth in a wide range of experientially relevant possible worlds (thesis (E) above).…”
Section: Transglobal Evidentialism-reliabilismmentioning
confidence: 97%
“…Such automatically accommodated implicit information is called morphological content (Horgan and Tienson 1996, Potrč 1999, 2000, Henderson and Horgan 2000. Transglobal evidentialism-reliabilism gives pride of place to the notion of strong evidential support, as explicated non-reliabilistically in terms of truth in a wide range of experientially relevant possible worlds (thesis (E) above).…”
Section: Transglobal Evidentialism-reliabilismmentioning
confidence: 97%
“…We will briefly sketch the relevant considerations, drawing upon an important, and still very influential, discussion of the matter in Fodor (1983) (for more extensive presentations see, in addition to Fodor 1983;Horgan and Tienson 1996;Henderson and Horgan 2000;Henderson and Horgan forthcoming;Fodor 2000;Horgan and Potrč 2008;and Horgan in press). 1 In the closing pages of Fodor (1983), it is argued that certain problems in classical cognitive science look to be in-principle problems, and hence that the prospects for understanding processes like belief fixation within the framework of classical cognitive science are very bleak.…”
Section: Background To the Problemmentioning
confidence: 98%
“…We also advocate a form of experiential evidentialism concerning epistemic justificationroughly, the view that the justification-status of an agent's beliefs is fully determined by the character of the agent's conscious experience. We two authors are each on record as defending both the thesis that much belief-formation is essentially morphological (e.g., Horgan and Tienson 1996;Henderson and Horgan 2000;Potrč 2000;Horgan and Potrč 2006;Horgan and Timmons 2007;Henderson and Horgan forthcoming), and also a version of evidentialism (Henderson et al 2007). …”
mentioning
confidence: 97%
“…Both of these features play an important role in the literature on implicit content (e.g. Lyons 2013, Henderson and Horgan 2000, and as we shall see they make for an apt characterization of the phenomenon. In order for the response from implicit content to work however, it has to be demonstrated that these features distinguish implicit contents from explicit contents: it should be impossible for explicit contents to have both these features and impossible for implicit contents to not have these features.…”
Section: Processes and Implicit Contentmentioning
confidence: 99%
“…Firstly, implicit contents are often said to be accommodated 'automatically' (Henderson andHorgan 2000: 516, Lyons 2013: 545). This is to say that cognitive systems act according to these contents whether we want them to or not.…”
Section: Automaticitymentioning
confidence: 99%